The economy of recognition: person, market and society in Antonio Rosmini - Hoevel, Carlos (2013)
Fil: Hoevel, Carlos. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Instituto de Investigación Francisco Valsecchi; Argentina